Facteurs institutionnels et developpement de la resistance aux trypanocides dans la zone cotonniere en Afrique de l'Ouest: Evidence empirique dans la province du kenedougou au Burkina faso - Ouédraogo, D.; Kamuanga, M.; Savadogo, K.; McDermott, John J.; Randolph, Thomas F.; Diarra, B.; Woitag, T.; Clausen, Peter-Henning (International Livestock Research Institute, 2004)
Trypanocidal treatments remain the most widespread method used for the control of African animal trypanosomosis (AAT). However increasing resistance affects the sustainability of this strategy. In general, resistance can be directly attributed to biological factors but it is recognized that institutional and socio-economic variables contribute greatly to the occurrence and Development of chemoresistance. This study uses data collected from 1998 to 2000 at farm level in the subhumid zone of Burkina Faso to investigate the role of socio-economic factors in the Development of trypanocidal drugs resistance. To assess relationships between factors and resistance, a dynamic Tobit model and a probit model were used to identify the determinants of treatments failures at farm level. The results suggest that age and educational level of the household head, and availability of transport for the household favour the occurrence of resistance to trypanocidal drugs. Environmental variables such as trypanosome prevalence in cattle and tsetse and a lagged variable of the previous rate of treatment failure are jointly associated with the presence of resistant trypanosomes. Although the direct causes of resistance are biological, socio-economic and institutional factors (market failures, inappropriate use of trypanocidal compounds by producers and untrained persons acting as professionals, including unregulated and excessive use of these compounds) are of crucial importance. Improved policies favouring integrated control to better manage resistance are required, as resistance is becoming a crucial constraint to livestock and agricultural productivity in the subhumid zone. Chemoresistance is a problem in Kenedougou province, where it is particularly important because of farmers' reliance on draught power.